Tumor rim cells: From resistance to vascular targeting agents to complete tumor ablation. Issue 3 (March 2017) - Seidi, Khaled; Jahanban-Esfahlan, Rana; Zarghami, Nosratollah
Current vascular targeting strategies pursue two main goals: anti-angiogenesis agents aim to halt sprouting and the formation of new blood vessels, while vascular disrupting agents along with coaguligands seek to compromise blood circulation in the vessels. The ultimate goal of such therapies is to deprive tumor cells out of oxygen and nutrients long enough to succumb cancer cells to death. Most of vascular targeting agents presented promising therapeutic potential, but the final goal which is cure is rarely achieved. Nevertheless, in both preclinical and clinical settings, tumors tend to grow back, featuring a highly invasive, metastatic, and extremely resistant form. This review highlights the critical significance of tumor rim cells as the main factor, determining therapy success with vascular targeting agents. We present an overview of different single and combination treatments with vascular targeting agents that enable efficient targeting of tumor rim cells and long-lasting tumor cure. Understanding the nature of tumor rim cells, how they establish, how they manage to survive of vascular targeting agents, and how they contribute in tumor refractoriness, may open new avenues to the development of beneficial strategies, capable to eliminate residual rim cells, and enable tumor ablation once and forever.